Gray Level Co-ocurence Matrix untuk Pengekstrasian Ciri Topeng Cirebon - Felix Indra Kurniadi; Vinnia Kemala Putri (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2020)
Cirebon mask is one of the intangible cultural heritage in Indonesia. It is one of the prominent cultural assets from Cirebon and becoming one of the identity Cirebon culture. However, the current condition people tend to forget the cultural asset and lack of help from the government makes the Cirebon mask become the third-rate assets. Our concern lays on the extinction of this Mask. We want to implement digitation and automatic identification using image processing techniques. In this paper, we applied the Gray Level Co-occurrence Matrix for extracting the features. K-Nearest Neighbour as the classifier. The best accuracy of this research is 40,67%